Analisis pengaruh Literasi Keuangan, Inklusi Keuangan, dan Financial Technology terhadap kinerja Usaha Mikro Kecil Menengah (UMKM) di Kota Bandung - Fadilah, Inne; Rahman, Sulaeman; Anwar, Mokhamad (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The important role of micro, small and medium enterprises (MSMEs) in the national economy can be seen from their contribution to Indonesia's Gross Domestic Product (GDP). The increase in the number of MSME actors still leaves several problems, including MSME actors in Indonesia still having performance problems. This study aims to examine the effects of financial literacy, financial inclusion, and financial technology on the performance of micro, small, and medium enterprises (MSMEs) in the city of Bandung. This research uses quantitative methods and is processed using the SmartPLS 3.0 analysis tool. The population in this study were all MSMEs registered in the cooperatives and MSMEs in Bandung City. The sampling technique used is purposive sampling. The number of samples in this study was 120 SMEs in the city of Bandung. The results of this study indicate that financial literacy, financial inclusion, and financial technology have a positive and significant impact on the performance of MSMEs in the city of Bandung.